Variable tilt-angle, parallel-hole collimation system for high-resolution molecular imaging gamma tomosynthesis. (November 2019) - Longo, Mariaconcetta; Pani, Roberto; Pellegrini, Rosanna; Nerina Cinti, Maria; Frantellizzi, Viviana; De Vincentis, Giuseppe
Highlights: The study proposes a gamma tomosynthesis imaging based on a variable tilt-angle collimator. Planar projection images are acquired and reconstructed through the Shift And Add method. Gamma tomosynthesis has superior spatial resolution and contrast compared to SPECT. The proposed system could help clinicians in detecting lesions at the bedside. Abstract: Purpose: This study investigates a novel gamma tomosynthesis (GT) method based on a variable tilt-angle, parallel-hole collimator (VAPHC) which, mounting to a conventional gamma, is able to perform high-resolution three-dimensional imaging. Methods: The VAPHC has the remarkable feature to be modular, consisting of independent collimation elements able to tilt according to variable angles [−45° to +45°]. Spatial resolutions were measured in reconstructed GT images using a point source at different source-to-collimator distances, while sensitivity was evaluated over the range of slant angles using a disk-source. Image contrast (IC) and contrast-to-noise-ratio (CNR) of sub-centimeters tumors were evaluated using a breast phantom containing a background activity and spheres filled with 99m Tc to simulate lesions at two depths. Breast phantom GT images were compared with planar and circular-orbit SPECT acquisitions of equal scan-time. Results: Planar spatial resolutions range from 9 to 14 mm over a depth range of 6–10 cm; spatial resolution in depth dimension becomes two times greater than those in the other dimensions. The measured sensitivity decreases from 9 cps/μCi to 6 cps/μCi varying the slant angle from 5° to 45°. The measured IC and CNR of GT reconstructed images demonstrated that it was possible to improve the spatial resolution/sensitivity trade-off. Conclusions: The proposed GT based VAPHC demonstrated the potential for superior spatial resolution and contrast compared to planar and SPECT acquisitions. A conventional gamma camera equipped with the VAPHC could be located at the minimum distance from the patient, thus improving detection, localisation and characterisation of sub-centimetre lesions.